Effective communication between school and family within the framework of educational co-responsibility - Bedoya Moscoso, Cristian Mauricio (GACETA DE PEDAGOGÍA, 2025)
This article focuses on the fundamental role that communication between family and school plays in the teaching and learning process of students in the City of Medellín. Its objective is to formulate a system to develop effective communication processes, thus contributing to collective awareness about the levels of coresponsibility in the search for structural improvement of education. This study was carried out within the framework of qualitative research, with emphasis on participatory action. The results were obtained using instruments such as focus groups, discussion groups, interviews and triangulation. The findings reveal that a closer and more constant exchange between guardians and teachers can improve students’ academic performance, encouraging greater participation in education.